#TITLE_ALTERNATIVE# - ROHARATUA HUTABARAT (NIM 15103006), INDRA
The Yogyakarta's earthquake that happened on 26 Mei 2006 caused by the Opak fault movement was the result of tectonical sloping plate on the subduction zone of the Australian and Eurasian plate. The earthquake results vibration wave called seismic wave. At present time, the characteristic of the seismic wave can be learned from the kinematic coordinate solution of GPS High-Rate station 1 second interval. Using the solving method of Pseudo Kinematic from Bernese Software with the GPS High-Rate data between Yogyakarta station (JOG2) and Diego Garcia station (DGAR) with approximately 4000 Km distance will be examined the problems because the influence of long baseline. From the result of GPS High Rate data processing can be concluded that the main problem for determining the characteristic of the seismic wave from long baseline is on determining the phase ambiguity resolution because the residual, error and bias still significant from bias (e.g : Ionosphere Bias, Troposphere Bias, Orbital Error) and the influence from the residual false on the coordinate solution.